Studying Micro to Millisecond Protein Dynamics Using Simple Amide (15)N CEST Experiments Supplemented with Major-State R(2) and Visible Peak-position Constraints - Khandave, Nihar Pradeep (J Biomol NMR, 2023)
Over the last decade amide (15)N CEST experiments have emerged as a popular tool to study protein dynamics that involves exchange between a ‘visible’ major state and sparsely populated ‘invisible’ minor states. Although initially introduced to study exchange between states that are in slow exchange with each other (typical exchange rates of, ~10 to ~400 s(-1)), they are now used to study interconversion between states on the intermediate to fast exchange timescale while still using low to moderate (~5 to ~300 Hz) ‘saturating’ B(1) fields. The (15)N CEST experiment is very sensitive to exchange as the exchange delay T(EX) can be quite long (~0.5 s) allowing for a large number of exchange events to occur making it a very powerful tool to detect minor sates populated (p(minor)) to as low as 1%. When systems are in fast exchange and the (15)N CEST experiments readily detect the minor states, the exchange parameters are often still poorly defined because the [Formula: see text] versus p(minor) and [Formula: see text] versus exchange rate (k(ex)) plots can be quite flat with shallow or no minima and the analysis of such (15)N CEST data can lead to wrong estimates of the exchange parameters due to the presence of ‘spurious’ minima. Here we show that the inclusion of experimentally derived constraints on the intrinsic transverse relaxation rates and the inclusion of visible state peak-positions during the analysis of amide (15)N CEST data acquired with moderate B(1) values (~50 to ~300 Hz) results in a convincing minimum in the [Formula: see text] versus p(minor) and the [Formula: see text] versus k(ex) plots even when exchange occurs on the ~100 μs timescale. The utility of this strategy is demonstrated on the fast-folding Bacillus stearothermophilus peripheral subunit binding domain that folds with a rate constant ~10,000 s(-1). Here the analysis of (15)N CEST data alone results in [Formula: see text] versus p(minor) and [Formula: see text] versus k(ex) plots that contain shallow minima, but the inclusion of visible-state peak positions and restraints on the intrinsic transverse relaxation rates of both states during the analysis of the (15)N CEST data results in pronounced minima in the [Formula: see text] versus p(minor) and [Formula: see text] versus k(ex) plots and precise exchange parameters even in the fast exchange regime k(ex)/|Δω| ~5). Using this strategy we find that the folding rate constant of PSBD is invariant (~10,500 s(-1)) from 33.2 to 42.9 °C while the unfolding rate (~70 to ~500 s(-1)) and unfolded state population (~0.7 to ~4.3%) increase with temperature. The results presented here show that protein dynamics occurring on the ~10 to ~10,000 s(-1) timescale can be studied using amide (15)N CEST experiments.